Evaluation of Readings of the Theory of Objectivity of Attributes with the Sprit with Emphasis on Ṣadrā’s Approach - Muhammad Ali Ismaili; Mehri Changi Ashtiani (آموزه‌‌های فلسفه اسلامي, 2021)
The most important challenge that has long been the focus of the theologians of the Abrahamic religions is the qualification (attribution) of the Sprit to the real positive attributes and how it is compatible with the simplicity of the essence in response to such views as “abundance of attributes over essence”, “deputyship of essence from attributes” and “objectivity of real attributes with essence” has been raised. The recent view, which has been accepted by many thinkers in Jewish, Christian and Islamic theology, has always been in a state of ambiguity, and various interpretations have been mentioned for it, the present of which deals with the interpretation and evaluation of the most important ones. It becomes clear through this article, that Ṣadr-ol-Mote'allehin, using the principles of transcendent wisdom (Ḥikmat al-muta'aliya), especially the realization of philosophical concepts and their state of joining closely in essence (Arabic: اندماج), has provided a profound interpretation of this theory, while accepting the conceptual change of attributes and essence and denying the negative representation of positive attributes knows them as the very existence of essence and its incorporation mode.